2014
DOI: 10.4236/fns.2014.57071
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Safety of Dried Fish Meat (<i>Kejeik</i>) Produced in Sudan

Abstract: The present study aimed to estimate the microbiological characteristics as well as the safety of traditionally fermented fish product, Kejeik. Kejeik samples were collected from Singah city (Blue Nile) and Kusti city (White Nile), Sudan. These samples were previously prepared from Ijl, Nawk and Garmut fish types. The microbiological analyses indicated that Kejeik products were devoid of any harmful bacteria like Salmonella, Listeria monocytogenes and Escherichia coli O157:H7. The highest count of aerobic bacte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 6 publications
1
9
0
Order By: Relevance
“…Salmonella was not detected in the samples analyzed in this study, which was in agreement with previous studies (Sulieman et al 2014) in seafood products. Meanwhile, disagreed with those of Soliman et al, (2002), Younis, (2013) who isolated Salmonella from fried fish, shrimp.…”
Section: A) Salmonellasupporting
confidence: 93%
“…Salmonella was not detected in the samples analyzed in this study, which was in agreement with previous studies (Sulieman et al 2014) in seafood products. Meanwhile, disagreed with those of Soliman et al, (2002), Younis, (2013) who isolated Salmonella from fried fish, shrimp.…”
Section: A) Salmonellasupporting
confidence: 93%
“…Similar prevalence of B. cereus was discovered in fesiekh spread samples. Bacillus cereus was previously isolated from traditionally fermented fish product (Kejeik), produced in Sudan (Sulieman et al, 2014). Based on FAO published notes, Bacillus cereus is a major etiological agent of food-borne outbreaks associated with fish and shellfish (Ryder et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Antibiogram was carried out as per the standard disk diffusion assay with 0.5 McFarland standard and break points interpretation were estimated with the help of CLSI manual (CLSI, 2012;2014). All the analyses for biochemical quality parameters were done in triplicate and the results are expressed as mean ± standard deviations.…”
Section: Microbiological Analysesmentioning
confidence: 99%
“…Consumption of such mycotoxins may give illness to the consumers. Enormous reported are available about the poor microbiological quality of fishes from dry fish markets of India and worldwide (Sulieman et al, 2014;Lilabati et al, 1999;Prakash et al, 2011). It has been observed that higher level of enterobacteria and faecal streptococci (FS) in the collected dry fish samples; it may due the drying of the fish in the unhygienic surface area.…”
Section: Dried Fishmentioning
confidence: 99%